Dimensions of Service Quality that Influence Online Ratings and Reviews at the Ascent Premiere Hotel in Pasuruan - Salsabila Fioletta Asshara; Sheidy Yudhiasta (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Advances in digital technology have transformed how customers obtain information and evaluate hotel services. Online ratings and reviews have become major information sources that influence customers' accommodation choices. This study aims to examine the influence of service quality dimensions on online ratings and reviews at the Ascent Premiere Hotel in Pasuruan. A quantitative approach was employed using the SERVQUAL model, comprising Tangibles, Reliability, Responsiveness, Assurance, and Empathy. Data were collected through questionnaires distributed to 100 respondents who had stayed at the hotel and used its services. Multiple linear regression analysis revealed that the five service quality dimensions simultaneously exert a significant influence on online ratings and reviews (F = 53.357, p < 0.001). The coefficient of determination (R² = 0.739) indicates that 73.9% of the variance in online ratings and reviews is explained by the proposed model. Partially, only Reliability and Empathy significantly influence online ratings and reviews, whereas Tangibles, Responsiveness, and Assurance show no significant effects. Empathy emerged as the most influential dimension, highlighting the importance of personalized attention, while Reliability emphasizes the role of consistent service delivery in encouraging positive customer evaluations. These findings suggest that strengthening interpersonal interactions and service consistency is essential for enhancing hotels' digital reputation..